Cognitive Radios and their Role in Efficient Allocationof the Spectrum - Thakur, Kavita; Dewangan, Nilesh Kumar (Richtmann Publishing, 2012)
Today’s wireless networks are characterized by fixed spectrum assignment policy. The limited availablespectrum and the inefficiency in the spectrum usage necessitate a new communication paradigm to exploitthe existing wireless spectrum opportunistically. This new networking paradigm is referred to as DynamicSpectrum Access (DSA) and cognitive radio networks. Cognitive radio is a paradigm for wirelesscommunication in which either a network or a wireless node changes its transmission or receptionparameters to communicate efficiently avoiding interference with licensed or unlicensed users. In practice,the spectrum allocated to licensed primary users is not utilized properly. The secondary unlicensed userscan sense and utilize the unutilized spectrum.